The Influence of Profitability, Liquidity, Inflation, and Interest Rates on Stock Returns of Infrastructure Sector Companies on The Indonesia Stock Exchange - Ni Putu Kartika Cahyani; Ni Putu Santi Suryantini (Asosiasi Riset Ilmu Manajemen Kewirausahaan dan Bisnis Indonesia, 2025)
Stock return refers to the gain that investors may obtain when allocating their funds in the capital market. The stock returns of infrastructure sector companies experienced consecutive declines over the three-year period from 2021 to 2023. These declines may be attributed to both internal and external factors affecting the companies. The purpose of this study is to examine the effects of profitability, liquidity, inflation, and interest rates on stock returns. This research was conducted on infrastructure sector companies listed on the Indonesia Stock Exchange for the period 2021–2023. The study employed quantitative data derived from secondary sources published by the Indonesia Stock Exchange and Bank Indonesia. The sample comprised all 56 companies in the population, selected using a saturated sampling method. The research employed a non-participant observation method. The analytical technique used was multiple linear regression. The results show that profitability has a positive and significant effect on stock returns, while liquidity, inflation, and interest rates do not have a significant effect on stock returns. These findings suggest that profitability serves as an important signal for investors when making investment decisions.